Salt stress affects germination and seedling establishment in different wheat (Triticum aestivum L.) varieties - Nazeer, Hina; Rauf, Mamoona; Gul, Humaira; Yaseen, Tabassum; Shah, Adnan Ali; Khushnood Ur Rehman (Journal of Pure and Applied Agriculture, 2023)
Salt stress is a very important factor worldwide as it reduces the agricultural production of many crops. This project was aimed to determine the effect of salt stress on the process of germination and seedling establishment of six Triticum aestivum varieties (Fakhr e Sarhad, Insaf, Lalma, Tatora, Bathoor, and Barsat). Five seeds of six Triticum aestivum cultivars were placed in each Petri-plate. Seeds were treated with different concentrations (0, 50 mM, and 150 mM) of NaCl. After 8 days, the experiment was terminated and germination percentage, seedling length, seedlings biomass were recorded, while relative water content (RWC), vigor index (VI), root shoot ratio (RSR), stem weight ratio (SWR), root weight ratio (RWR), and stress tolerance index of different parameters were calculated. Analyzing results, it was observed that salt stress damage plant at observed stages in the form of the